1991
DOI: 10.1007/bf02351198
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of parental reaction to student grades

Abstract: Abstract. Factor analysis of questionnaire responses produced by over 6,000 individuals revealed parental reactions to good and bad grades grouped themselves into five categories: (1) Grades are important to me; bad ones lead to negative consequences; (2) Good grades are important to me, but I will support you regardless of grade; (3) Bad grades make me mad; (4) Do your best, but there is more to life than grades; and (5) Grades are important; you will know how I feel on the basis of a joking comment. When the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…Our findings also indicated that they were some contradicting exceptions to this as, 28.7% of candidates said yes to parent's disproval to bad grade. The same study from US also concurs with 13% parents nagging and showing anger to low grades (Pollio et al, 1991). Taken together, we can conclude that this mindset of parents focuses more on the child's ability to perform rather than learning itself (Haimovitz & Dweck, 2016).…”
Section: Conclusion and Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our findings also indicated that they were some contradicting exceptions to this as, 28.7% of candidates said yes to parent's disproval to bad grade. The same study from US also concurs with 13% parents nagging and showing anger to low grades (Pollio et al, 1991). Taken together, we can conclude that this mindset of parents focuses more on the child's ability to perform rather than learning itself (Haimovitz & Dweck, 2016).…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…Data analysis also revealed that when students were asked if their parents do not react well to bad grades, 40% disagreed. The study from US further validated our results as 42% of parents supported their children and wanted them to perform and be the "best" regardless of their grade (Pollio et al, 1991). Our findings also indicated that they were some contradicting exceptions to this as, 28.7% of candidates said yes to parent's disproval to bad grade.…”
Section: Conclusion and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Date Signature of Evaluator studies of parent perceptions of grading procedures (Culbertson & Jalongo, 1999;Munk & Bursuck, 2001;Pollio, Humphreys, & Eison, 1991;Shepard & Bliem, 1995); student perceptions of grading procedures (Bursuck, Munk, & Olson, 1999;Zeidner, 1987); and various perceptions of assessment and grading (Carlton, 1993;Colangelo, 1981;Donegan & Trepanier-Street, 1998;Viadero, 1994) and report card reform (Allison & Friedman, 1995a, 1995bPardini, 1997). Most of these studies examined perceptions at the secondary level and none reported perceptions of assessment in music courses.…”
Section: Thomas Jeffers September 21 2001 Signature Of Staff Membermentioning
confidence: 99%